EDIBLE FILM DARI KARAGENAN DAN MINYAK CENGKEH SEBAGAI ANTIMIKROBA PADA IKAN SEGAR - Jaja, Ali; Putri, R. Marwita Sari; Jumsurizal, Jumsurizal (Marinade, 2021)
Edible film is a type of packagingthat is both effective and safe. Edible film maked using natural ingredients such as carrageenan. Clove oil addetional to enhance its antimicrobial function. This study puposed to determine the effect of using carrageenan and clove oil concentrations in the organoleptic and ALT test. The design used was used was CRD with test parameter namely thikness tset, elongation, tensile strenght, organoleptic quality obcervation and ALT. Thikness test result 0.02-0.13 mm, elongation 1.027-1.117%, tensile strength 0.088-0.095 MPa, the best organoleptic is A2 on parameter (eyes, smell and texture), ALT A1 value (1.4x103 koloni/g) amd A2 (9.4x102 koloni/g). the reduction of carrageenan and additional of clove oil resulted in increased thikness and tensile strenht, while decreasing elongation. Based on the organoleptic test, the best the best treatment was edible film A2. ALT A1 and A2 test result do not exceed the threshold.